2020
DOI: 10.1177/0018726719900009
|View full text |Cite
|
Sign up to set email alerts
|

When is age dissimilarity harmful for organisational identification? The moderating role of age stereotypes and perceived age-related treatment

Abstract: Due to demographic changes, age diversity is growing in the workplace, creating a potential challenge to social integration. However, who is most affected by working with colleagues of different ages and when is being dissimilar in age from others more likely to hinder organisational identification? Drawing on relational demography and on the social identity approach, we suggest that certain individual and contextual conditions can lead employees to react to greater age dissimilarity by reducing their psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…This study adds to ongoing research in this area by showing that age diversity has another highly important benefit for teams in that it moderates the effect of high performers on team performance. The study sheds light on one way in which high performers who are older than other team members can be more valuable for their teams than their younger counterparts (Pritchard & Whiting, 2014; Sammarra et al, 2020). This finding is arguably particularly important because of the general discrimination older individuals often face in organizations (Muller-Camen et al, 2011; Posthuma & Campion, 2009; Standifer et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…This study adds to ongoing research in this area by showing that age diversity has another highly important benefit for teams in that it moderates the effect of high performers on team performance. The study sheds light on one way in which high performers who are older than other team members can be more valuable for their teams than their younger counterparts (Pritchard & Whiting, 2014; Sammarra et al, 2020). This finding is arguably particularly important because of the general discrimination older individuals often face in organizations (Muller-Camen et al, 2011; Posthuma & Campion, 2009; Standifer et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Moderating effect of age on technology aids, knowledge sharing, and research output Extending the above arguments, it is believed that the legacy of KS between older and younger employees is crucial for knowledge retention in an organization (Burmeister and Deller, 2016). The literature recognizes age as an important factor in determining the relationship between employees' psychological state and workplace behavior (Sammarra et al, 2021). While studying the moderating effect of age on the relationship between an employee' psychological state and KS, Chen et al (2021) found out that with aging, the employee psychological state had a reduced effect on knowledge collecting and donating.…”
Section: Relevance Of Technology Aids For Research Output Of Younger ...mentioning
confidence: 99%
“…Extending the above arguments, it is believed that the legacy of KS between older and younger employees is crucial for knowledge retention in an organization (Burmeister and Deller, 2016). The literature recognizes age as an important factor in determining the relationship between employees' psychological state and workplace behavior (Sammarra et al. , 2021).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Whereas the general assumptions of social identity and self-categorization theories overlap-they both imply that age differences trigger the formation of in-and outgroups based on age-their theoretical focus is different (Hornsey & Hogg, 2000). Specifically, the self-categorization perspective focuses on harmful intergroup processes, whereas the social identity perspective focuses on why social categorizations occur (Hogg & Terry, 2000)-that is, people's fundamental desire for a positive social identity through their belongingness to a distinct social in-group (Sammarra et al, 2021;Shore et al, 2011). This calls for a different and ultimately more nuanced view on the link between age separation and turnover.…”
Section: Social Identity Perspectivementioning
confidence: 99%